PENGETAHUAN ORANG TUA DALAM TOILET TRAINING SEBAGAI FAKTOR KEJADIAN ENURESIS PADA ANAK USIA PRASEKOLAH - Rifatul Hasanah, Viki; Munir, Zainal; Tauriana, S. (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Enuresis, or bedwetting, is an elimination disorder commonly experienced by preschool-aged children and may negatively affect both their physical and psychological well-being, including feelings of shame, low self-esteem, and social difficulties. One of the factors influencing the occurrence of enuresis is the success of toilet training, which is highly dependent on parental knowledge and active involvement, particularly that of mothers. Limited parental knowledge may lead to delayed toilet training and increase the risk of enuresis. Objective: This study aimed to analyze the relationship between parents’ knowledge regarding toilet training and the incidence of enuresis among preschool-aged children. Methods: This study employed a quantitative approach with a cross-sectional design. The study population consisted of all parents with preschool-aged children in two research locations. A total sampling technique was used, resulting in 169 respondents. Data were collected using a toilet training knowledge questionnaire and an enuresis incidence questionnaire. Data analysis was performed using the Spearman Rank test. Results: The majority of parents had a moderate level of knowledge regarding toilet training. The incidence of enuresis among preschool-aged children remained relatively high. Statistical analysis showed a significant relationship between parents’ level of knowledge about toilet training and the incidence of enuresis. Conclusion: Adequate parental knowledge regarding toilet training plays an important role in reducing the incidence of enuresis among preschool-aged children. Continuous education and assistance are needed to help parents implement toilet training appropriately and consistently.